2018
DOI: 10.35608/ruraled.v27i2.497
|View full text |Cite
|
Sign up to set email alerts
|

Rural School Consolidation

Abstract: The consolidation of rural schools in the United States has been a controversial topic for policy-makers, school administrators, and rural communities since the 1800s. At issue in the consolidation movement have been concerns of efficiency, economics, student achievement, school size, and community identity. Throughout the history of schooling in America, school consolidation has been a way to solve rural issues in the eyes of policy makers and many education officials. Today, faced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This development approach reinforced the role of schools as community anchors that, over time, came to also serve as sites for the delivery of essential community services and for hosting important community events for nearby residents (Vincent, 2006). Indeed, in many communities, especially in small town and rural contexts, schools are so deeply connected to multiple generations of residents' lives that they represent a critical piece of community identity (Bard et al, 2006; Tieken, 2014). Because of the multi‐faceted roles that public schools play in citizens' lives, their enduring presence offers stability to communities that is unmatched by any other public institution.…”
Section: School Closuresmentioning
confidence: 99%
“…This development approach reinforced the role of schools as community anchors that, over time, came to also serve as sites for the delivery of essential community services and for hosting important community events for nearby residents (Vincent, 2006). Indeed, in many communities, especially in small town and rural contexts, schools are so deeply connected to multiple generations of residents' lives that they represent a critical piece of community identity (Bard et al, 2006; Tieken, 2014). Because of the multi‐faceted roles that public schools play in citizens' lives, their enduring presence offers stability to communities that is unmatched by any other public institution.…”
Section: School Closuresmentioning
confidence: 99%
“…Next, we obtained open enrollment numbers, a measure of how attractive parents find in‐district schools. Finally, we identified critical events from conversations with stakeholders (e.g., city administrators and teachers), as well as literature review (Bard et al, 2005; Pride, 2002) and news articles following exploratory data analysis (next section). Those events amounted to precedents (e.g., high taxes relative to surrounding districts) and ramifications (e.g., school closures) of school reorganization initiatives.…”
Section: Datamentioning
confidence: 99%
“…Some residents, for instance, may prefer to merge with a different (adjacent) school district which has more suitable programming or a lower tax rate (Niehaus-Steffensmeier, 2018). Other residents may dread school closures, a common occurrence in school reorganization and widely regarded as highly detrimental to the local economy: following a review of the literature on rural school reorganization, the National Rural Education Association Consolidation Task Force concluded that "after a school closure, out migration, population decline, and neighborhood deterioration are set in motion, and support for public education diminishes" (Bard et al, 2005). And Anderson (2009) observes, Iowa is no exception.…”
Section: Exploratory Data Analysis and Feature Engineeringmentioning
confidence: 99%
“…Throughout the 20th century, however, school closure and consolidation have remained a constant aspect of school reform efforts, resulting in an ongoing debate about the cost-effectiveness of maintaining small, rural schools, and whether the money saved through consolidation efforts are negated by lost tax dollars and deflated property values (Lyson, 2002). While suburban and urban school districts have also been subjected to consolidation efforts, rural schools have been traditionally seen as less cost-effective because of high administrative and transportation costs and less capable of providing quality educational services (Bard, Gardener, & Wieland, 2005; Strange, 2011), resulting in reform efforts that have greatly reduced the number of rural schools and school districts. School district consolidation, typically, brings together several smaller school districts to create one larger school district (Cox & Cox, 2010), often in an effort to reduce administrative costs, improve efficiency, and increase educational opportunities (Arnold, 2000; DeYoung & Howley, 1990; Duncombe & Yinger, 2007; Fairman & Donis-Keller, 2012).…”
Section: Case Narrativementioning
confidence: 99%